Integration of geo-referenced data for visual simulation in location-based mobile computing - Dias, J.; undefined; Pedro, S. (Computer-Aided Civil and Infrastructure Engineering, 2006)
Mobility is an emerging concept in the GIS (geographic information systems) domain and will eventually introduce a revolution in the way GIS users interact with their geo-referenced data. In this article, we propose a system architecture for a global, fully mobile and location-based GIS system, supporting geo-referenced data with multiple levels of abstraction, ranging from satellite imagery and airborne imagery, to GIS mapping, 3D volumetric models and augmented reality, with various levels of detail as well as multiple forms of visualization and interaction.